Relationship of arginine with lysine in diets for laying Japanese quails - Reis,Renata de Souza (2012)
To determine the relationship of arginine with lysine for Japanese quails during the period of production, an experiment was conducted using 360 subspecies of Japanese quails (Coturnix coturnix japonica) with 162 days of age, distributed in a completely randomized design. Diets were formulated with corn, soybean meal, sorghum and wheat bran containing 20.0% crude protein and 2,800 kcal ME/kg. The basal diet contained suboptimal level of lysine equal to 1% and was supplemented with five levels of L-arginine 99% (0.032; 0.083; 0.134; 0.185 and 0.236%) to replace the glutamic acid, corresponding to the relationship of arginine with digestible lysine of 1.16, 1.21, 1.26, 1.31 and 1.36. The parameters studied were: feed intake, egg production per hen/day, egg production per hen housed, commercial egg production, egg weight, egg mass, feed conversion by egg mass, feed conversion per dozen eggs, weight and percentage of components of the eggs (yolk, albumen and shell) and specific gravity. There was no significant effect on the relationship of arginine with digestible lysine in the diet of Japanese quails for any of the parameters examined. The arginine/lysine ratio of 1.16, which corresponds to a daily intake of 288.84 mg of arginine, provides satisfactory performance and egg quality of Japanese quails.